Ictal eructation in a case of idiopathic generalized epilepsy - Amirtha Shekar; Sreekanth Koneru; Charles Ákos Szabó (Epilepsy & Behavior Reports)
We present a 57 year-old right-handed female with a history of idiopathic generalized epilepsy since age two years old as well as mild-to-moderate intellectual impairment and behavioral dyscontrol. She was seizure free for many years on ethosuximide, but her absence seizures recurred as her dose was gradually decreased. After raising her dose, she also began to experience falls, at times with decreased responsiveness. She was admitted for inpatient video-EEG monitoring for quantification of her absence seizures and characterization of her falls. Our patient had 3–6 absence seizures per hour. In addition to a brief alteration of awareness, her absence seizures were frequently associated with belching and eyelid myoclonia lasting for 3–4 s. Her belching was correlated with a generalized ictal discharge and was not noted interictally. Several episodes of unsteadiness were noted, at times the patient falling backwards into her bed, but never falling to the ground from a standing position; none of these episodes associated with ictal EEG correlate. In summary, our patient demonstrated and absence seizures with ictal eructation or belching, which has not been reported as an ictal symptom of generalized seizures, and episodes of unsteadiness of unknown characterization.